Using Supplemental Lighting to Grow Hemp in Florida - Johan Desaeger; Jacqueline Coburn; Shinsuke Agehara (EDIS)
With the removal of hemp from the controlled substances list, hemp is now one of the emerging crops in Florida. There is limited information on how to grow this crop in Florida. Like hops, hemp is another recently introduced crop in the state, with one of the major yield-limiting factors of premature flowering induced by inadequate day length. This article provides guidelines for hemp growers in Florida on the use of supplemental lighting to control flowering and improve growth of hemp under Florida’s environmental conditions. Written by Johan Desaeger, Jacqueline Coburn, and Shinsuke Agehara, and published by the UF/IFAS Horticultural Sciences Department; 4 pp. https://edis.ifas.ufl.edu/hs1452